2019
DOI: 10.1111/1750-3841.14787
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus Casei YBJ02 on Lipid Metabolism in Hyperlipidemic Mice

Abstract: Traditionally fermented yak yogurt as a Tibetan dairy product is high not only in nutrients but also in probiotics. A probiotic strain with a potential lipid reducing effect was isolated from yak yogurt. An animal model for hyperlipidemia was evaluated using the blood index and expression levels of lipid metabolism-related proteins in mice to determine the effect of Lactobacillus casei YBJ02 (LC-YBJ02) on lipid metabolism in hyperlipidemic mice and the underlying mechanism. LC-YBJ02 at different concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 47 publications
1
15
0
1
Order By: Relevance
“…Like Bifidobacteriaceae, several probiotic species of the Lactobacillaceae family have been shown to either prevent or alleviate hepatic lipid accumulation in rodent models of fatty liver disease, obesity or metabolic syndrome. 54,55 Further characteristic changes in the gut microbiota composition at the family level in group O3.0 were increases of Erysipelotrichaceae (Firmicutes phylum), Prevotellaceae (Bacteroidetes phylum) and Sutterellaceae (Proteobacteria phylum) and decreases of Anaeroplasmataceae (Tenericutes phylum), Desulfovibrionaceae (Proteobacteria phylum), Eubacteriaceae, Ruminococcaceae (both Firmicutes phylum) and Saccharibacteria (Candidatus saccharibacteria phylum). Despite the biological meaning of all of these gut microbiota modifications induced by cuticle supplementation is unclear, similar changes in several of these bacterial populations (increases of Prevotellaceae, Bifidobacteriaceae and Coriobacteriaceae, decrease of Desulfovibrionaceae) are in line with those found in other obese rodent models, in which antisteatotic and hepatoprotective effects have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Like Bifidobacteriaceae, several probiotic species of the Lactobacillaceae family have been shown to either prevent or alleviate hepatic lipid accumulation in rodent models of fatty liver disease, obesity or metabolic syndrome. 54,55 Further characteristic changes in the gut microbiota composition at the family level in group O3.0 were increases of Erysipelotrichaceae (Firmicutes phylum), Prevotellaceae (Bacteroidetes phylum) and Sutterellaceae (Proteobacteria phylum) and decreases of Anaeroplasmataceae (Tenericutes phylum), Desulfovibrionaceae (Proteobacteria phylum), Eubacteriaceae, Ruminococcaceae (both Firmicutes phylum) and Saccharibacteria (Candidatus saccharibacteria phylum). Despite the biological meaning of all of these gut microbiota modifications induced by cuticle supplementation is unclear, similar changes in several of these bacterial populations (increases of Prevotellaceae, Bifidobacteriaceae and Coriobacteriaceae, decrease of Desulfovibrionaceae) are in line with those found in other obese rodent models, in which antisteatotic and hepatoprotective effects have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that continuous intake of high‐glucose‐fat diets can lead to abnormal lipid metabolism in T2DM rats, especially an increase in circulating FFAs, which is a typical characteristic of insulin resistance (DeFronzo & Tripathy, 2009; Hsieh et al, 2018). As compared with the D and GS18 groups, the serum levels of TC, TG, and LDL‐C were significantly improved in the SS18‐5 group, which may have been due to the fact that bacteria can promote the excretion of free cholic acid and reduce serum cholesterol content and the absorption of cholesterol (Qian et al., 2019; Zeng et al.,2010). L .…”
Section: Discussionmentioning
confidence: 99%
“…qPCR mixture was prepared with 1 μl of SYBR Green PCR Master Mix (Thermo Fisher Scientific, Inc., Waltham, MA, USA), 2 μl of the obtained cDNA template, and 1 μl of both forward and reverse primer each (Table 2). Up to 40 qPCR cycles were performed after the following reaction conditions: 95°C, 60 s; then 95°C, 15 s; 55°C, 30 s; 72°C, 35 s; and 95°C, 30 s; 55°C, 35 s. With GAPDH as a reference parameter, the relative expression levels of target genes were determined by the following formula: 2 –ΔCT = ΔCT (detection gene) ‐ΔCT (GAPDH) (Qian et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…. Up to 40 qPCR cycles were performed after the following reaction conditions: 95°C, 60 s; then 95°C, 15 s; 55°C, 30 s; 72°C, 35 s; and 95°C, 30 s; 55°C, 35 s. With GAPDH as a reference parameter, the relative expression levels of target genes were determined by the following formula: 2 -ΔCT = ΔCT (detection gene) -ΔCT (GAPDH)(Qian et al, 2019).…”
mentioning
confidence: 99%